(untitled) (Scripta Theologica, 2020)
Biblical scholars tend to believe that prophets addressed the issue of their call for apologetic reasons: to justify his authority, a contested prophet mentioned his being called by God to spread God’s word. The current form and location of prophetic call narratives within prophetic books is, however, a result of the activity of the prophets’ disciples and not the prophets themselves. Hence, three different communicational situations may be distinguished in the prophetic call narratives, whose subjects are in turn the prophet, his disciples and finally the text itself. The chain of testimonies of the original event of the prophecy did not end with the writing down of the narrative but continues to exist due to the existence of new listeners (readers). The prophet’s testimony of his call does not have as its aim the defence of the prophet’s authority or the legitimization of his word. Sharing his experience of the call, the prophet introduces his listeners to direct contact with God’s word to enable them to make a decision whether or not to listen to the word. As a result, the event founding the prophecy is performed and updated in the time and space of the new listeners of the prophetic word.